2018
DOI: 10.1590/s1806-37562016000000312
|View full text |Cite
|
Sign up to set email alerts
|

Sequential analysis as a tool for detection of amikacin ototoxicity in the treatment of multidrug-resistant tuberculosis

Abstract: Objective:To investigate early detection of amikacin-induced ototoxicity in a population treated for multidrug-resistant tuberculosis (MDR-TB), by means of three different tests: pure-tone audiometry (PTA); high-frequency audiometry (HFA); and distortion-product otoacoustic emission (DPOAE) testing. Methods:This was a longitudinal prospective cohort study involving patients aged 18-69 years with a diagnosis of MDR-TB who had to receive amikacin for six months as part of their antituberculosis drug regimen for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The bibliometric analysis of the top authors per country for the PTB and DR/MDR-TB categories are summarized in Table 3. For both categories, it is evident that the Brazilian Tuberculosis Research Network plays a leading role in Brazil, 14 - 19 whereas the Peruvian Partners in Health Research Network and Harvard University play major roles in Peru 20 23 In Argentina, Mexico, and Colombia, most of the basic research studies are conducted at a few high-level institutions, often in collaboration with other countries within and outside of Latin America.…”
Section: Resultsmentioning
confidence: 99%
“…The bibliometric analysis of the top authors per country for the PTB and DR/MDR-TB categories are summarized in Table 3. For both categories, it is evident that the Brazilian Tuberculosis Research Network plays a leading role in Brazil, 14 - 19 whereas the Peruvian Partners in Health Research Network and Harvard University play major roles in Peru 20 23 In Argentina, Mexico, and Colombia, most of the basic research studies are conducted at a few high-level institutions, often in collaboration with other countries within and outside of Latin America.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment for FGM is often complicated due to the side effects of antibiotic therapy, especially the amikacin ototoxicity 18 . Normally, aminoglycosides predominantly affect a portion of the inner ear, the cochlear and labyrinth hair cells, which may cause permanent hearing loss or tinnitus secondary to the degeneration of cochlear sensory hair cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies conducted on the patients who had been treated with ototoxic medications have shown that EHF audiometry and DPOAE measurements can detect evidence of ototoxicity in the inner ear earlier than conventional audiometry, potentially serving as a predictor to ototoxic effects prior to damage occurs in frequencies that are critical for speech and language comprehension (10, 16, 17).…”
Section: Introductionmentioning
confidence: 99%